Estudio preliminar de algunos insectos y ácaros, plagas en el cultivo de la yuca (Manihot esculenta,Crantz ) en el Estado Zulia, Venezuela - Quiros, Magally (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2014)
A preliminary study of several insects and mites found on Cassava plants, Manihot esculenta Crantz, is presented. In order to carried out this research it was necessary to visit 32 farms, located in the distrits of Maracaibo, Mara, Páez, Perijá, Baralt and Colón in Zulia State from April 1972 to September 1973. A total of 18 phytophagous arthropods and 11 among parasites and predators were identified; these last one are shown in a separate listo There is also presented in this paper another list of insects and mites found on “Cassava”, which was prepared using as a reference the literature for this crop in Venezuela and other countries. Some notes are given about the description, habits, damages, and economical importance of each specimen, as well as the methodology followed in the field and laboratory. From the observations made it can be stated that there are insects and mites which are important pests, like Chilomima clarkeí (Amsel), which is broadly spread in Zulia State; Mononychellus caribbeanae (McGregor) and various species of the genus Tetranychus which cause damages during the dry weather. The damage caused by Erinnyis ello is common for this crop, and in sorne cases it may destroy a plantation, specially when they come in large numbers. There are also other pests that might become dangerous in Manihot esculenta which are referred in this paper.